UJI KOMBINASI PUPUK ORGANIK DAN ANORGANIK DALAM POLA LEISA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM LOKAL PADA LAHAN MARGINAL - Leomo, Sitti; Sutariati, Gusti Ayu Kade; Agustina, Agustina (Jurnal Agroteknos, 2012)
The experiment was aimed to know the effect of combination of organic and anorganic fertilizers on growth and yield of local sorghum crops on dry land. The experiment was conducted in Kambu District Poasia and Agrotechnology Laboratory, Faculty of Agriculture University of Haluoleo, from August to December 2011. The experiment was arranged on randomized block design (RBD), which consisted of 7 treatments namely: control (A), 5 tons ha-1 of organic fertilizer (B), anorganic fertilizer (200 kg ha-1 urea, 100 kg ha-1 SP36 and 50 kg ha-1 KCl) (C), organic + anorganic fertilizer full recommended dosage (D), organic fertilizer +1/2 recommended dosage of anorganic fertilizer (E), organic fertilizer + ¼ recommended dosage of anorganic fertilizer (F) and organic fertilizer + 1/8 recommended dosage of anorganic fertilizer (G). Each treatment was repeated 3 times, therefore overall there were 21 experimental units. Data obtained were analyzed using analysis of variance and followed by Duncan’s Multiple Range Test. The research results showed that the combination of organic and anorganic fertilizers provided a significant influence on growth and yield of sorghum crops. Treatment of organic fertilizer + ½ recommended dosage of anorganic fertilizer (organic fertilizer 5 ton ha-1 + anorganic fertilizer 100 kg ha-1 Urea, 50 kg ha-1 SP36dan 20 kg ha-1 KCl) gave better effects on the observed variables: plant height, stem diameter, leaf number, leaf area, dry weight of plant biomass, panicle length, fresh weight of panicle, grain weight and the weight of 1000 seeds of sorghum. Keywords: combination of organic and anorganic fertilizers, rhizobakteria, sorghum